The power of music - North, Adrian; Hargreaves, David (The British Psychological Society, 2009)
The digital revolution has led to music being increasingly integrated into the stream of daily life. This inturn has led to researchers showing greater interest in the effects of music on a wide range of thoughts and behaviours. This article looks at three potential roles of music; namely, in selfinjurious behaviours; in reducing pain and increasing immunity; and in promoting animal welfare.